AN IMPROVING THE RELIABILITY OF TRANSFORMER WINDING PROTECTION SYSTEM BASED ON WIRELESS DATA COMMUNICATION - M. Faisol Agus Setiawan; Hamdani Hamdani; Amani Darma Tarigan (Jurnal Scientia, 2023)
Thermal effects arise due to winding transformers operating for medium or large power above 1 kVA. When this transformer is used continuously and heat effects continue to arise, it can lead to reduced power efficiency and increased distortion and a high possibility of failure in the transformer. By designing an additional cooling system, namely regulating fan rotation using the PID method using a thermocouple sensor, it can respond to optimal variations to move the fan at a certain rotation according to the heat level produced by the transformer operation with a maximum delay time of 3 minutes 20 seconds. Besides that, the temperature display and settings can be monitored using wireless communication, for ease of operation of the transformer.